The economics of development and planning - Jhingan, M. L. (Delhi : Konark Publishers PVT, 1995)
The book examines the problems of economic development of underdeveloped countries. This edition has been revised and enlarged. A new chapter on sustainable development has been added to part one and some diagrams are redrawn and their explanations simplified.
Includes bibliographical references.
nmn 28/03/17
Loans
Keywords: Economic development; Economic policy; Developing countries